2016
DOI: 10.1007/s11605-016-3274-0
|View full text |Cite
|
Sign up to set email alerts
|

Patient Adherence and Experience with Extended Use of Prophylactic Low-Molecular-Weight Heparin Following Pancreas and Liver Resection

Abstract: Patients reported high adherence and a manageable experience with post-operative extended-duration LMWH in an ambulatory setting following liver or pancreas resection. These findings suggest that patient adherence is not a major contributor to poor compliance with VTE prophylaxis guidelines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 34 publications
2
24
1
Order By: Relevance
“…Clearly, several questions remain unresolved with regard to the optimal dosing, timing and duration of LMWH treatment to achieve inhibition of tumour growth. Adherence rates were estimated to 85% using the anti-FXa assay, which is consistent with a study by Lemke et al [28], reporting adherence rates of 81% in patients with cancer completing a 4-week course of prophylactic enoxaparin following pancreatic or liver resection. In the literature, adherence rates of !80% are often considered acceptable [29e31], which supports the conclusion that the participants in the RASTEN trial were adequately adherent to LMWH.…”
Section: Discussionsupporting
confidence: 88%
“…Clearly, several questions remain unresolved with regard to the optimal dosing, timing and duration of LMWH treatment to achieve inhibition of tumour growth. Adherence rates were estimated to 85% using the anti-FXa assay, which is consistent with a study by Lemke et al [28], reporting adherence rates of 81% in patients with cancer completing a 4-week course of prophylactic enoxaparin following pancreatic or liver resection. In the literature, adherence rates of !80% are often considered acceptable [29e31], which supports the conclusion that the participants in the RASTEN trial were adequately adherent to LMWH.…”
Section: Discussionsupporting
confidence: 88%
“…Sixteen studies evaluated patient RIOs for the burden associated with treatments. 24,32,39,40,[43][44][45][46][47][51][52][53][54]60,65,80 One study, including patients taking long-term anticoagulation, reported that only some (12%) patients using direct oral anticoagulants (DOACs) may switch to VKAs because of complications and fear of adverse effects, as well as for not being reimbursed (subgroup of 19 participants from 1 study including 1001 total participants; low certainty) 65 (Table 4). With regard to the use of oral VKAs in general, although routine monitoring does not seem to represent a limitation for patients accepting it, many (58-64%) would switch to another anticoagulant if it were equally effective and required less monitoring or dietary restrictions (2070 participants from 5 studies; low certainty) 40,45,47,52,65 (Table 4).…”
Section: Nonutility Resultsmentioning
confidence: 99%
“…Treatment burden of injection (Lemke et al, 51 Maxwell et al, 53 Noble et al, 54 Trade-off between treatment burden and benefits with LMWH (Cajfinger et al, 46 Noble et al 54 ) Cancer patients place highest value on "the interference with cancer treatment," followed by "efficacy of the VTE treatment" and "risk for major bleeding." They place low value on monitoring through blood tests, frequency of administration, mistakes, and costs.…”
Section: Cancermentioning
confidence: 99%
“…Moreover, our results are limited by the primary studies. While adherence could be an important issue in an injectable medication such as tinzaparin, unlike trials observing the use of LMWH following surgery in patients with cancer, 23 none of the included trials reported on the adherence of the patients to assessed treatments. Furthermore, the number of events in all meta-analyses we performed was low.…”
Section: Discussionmentioning
confidence: 99%